Risk factors of infection with SARS-CoV-2 Omicron BA.1 in Indonesia - Utami, Windi Nurdiana; Simanjorang, Chandrayani; Maghfiroh, Adzkia Avisena; Andriana, Bunga; Lestari, Mugi Rahayu (Intelektual Pustaka Media Utama, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to mutate in Indonesia. The Omicron variant tends to have more cases but research related to this topic is still difficult to find. This study aimed to determine the risk factors for exposure to the Omicron variant of the SARS-CoV-2 virus. This study used a cross-sectional study design from SARS-CoV-2 surveillance data of the DKI Jakarta Health Office with a research sample of 3,480. Data analysis using Chi-square test followed by logistic regression test. The results found that men had a 1.82 higher risk of contracting the Omicron variant of SARS-CoV-2 than women. Elderly and adults had a 16.99 higher risk and 4.71 higher risk of developing the SARS-CoV-2 Omicron variant compared to children (p-value <0.05). People with a history of hypertension, diabetes mellitus, and cardiovascular had a 3.06, 3.05, and 4.56 higher risk of being infected with the Omicron variant of SARS-CoV-2 than those without a history of these comorbidities. It was concluded that the variable age is the riskiest factor. Vaccination does not reduce the risk of possible exposure to the Omicron variant, especially for those who are elderly, have a history of concomitant diseases, and are male.